Gut-spine axis: a possible correlation between gut microbiota and spinal degenerative diseases - Morimoto, Tadatsugu; Kobayashi, Takaomi; Kakiuchi, Toshihiko; Esaki, Motohiro; Tsukamoto, Masatsugu; Yoshihara, Tomohito; Hirata, Hirohito; Yabuki, Shoji; Mawatari, Masaaki (Frontiers in Microbiology, 2023)
As society ages, the number of patients with spinal degenerative diseases (SDD) is increasing, posing a major socioeconomic problem for patients and their families. SDD refers to a generic term for degenerative diseases of spinal structures, including osteoporosis (bone), facet osteoarthritis (joint), intervertebral disk degeneration (disk), lumbar spinal canal stenosis (yellow ligament), and spinal sarcopenia (muscle). We propose the term “gut-spine axis” for the first time, given the influence of gut microbiota (GM) on the metabolic, immune, and endocrine environment in hosts through various potential mechanisms. A close cross-talk is noted between the aforementioned spinal components and degenerative diseases. This review outlines the nature and role of GM, highlighting GM abnormalities associated with the degeneration of spinal components. It also summarizes the evidence linking GM to various SDD. The gut-spine axis perspective can provide novel insights into the pathogenesis and treatment of SDD.